«El libro en blanco» by Julio Ramón Ribeyro: the motif of the killer book - Quichiz Campos, Gustavo Alberto (Amaltea. Revista de Mitocrítica, 2018)
This work analyzes one of the more frequent keys of plausibility in a fantastic story: the magic object, specifically, in the motif of the killer book. It’s presented a recap of the motif from the myths, passing through chivalric literature, until the present day. It is also analyzed «El libro en blanco» by Julio Ramón Ribeyro, a story that presents us a book that only brings misfortunes to its possessors and whose main innovation is the book’s capacity of being the agent of its own perversity. The metaliterary of the story makes its analysis inevitable in relation to the novelistic creation in Ribeyro.